Radio Pathological Correlation of Thyroid Nodules Using Tirads Based Ultrasound Classification and Bethesda Classification for FNAC: a Prospective Study - Richa TIWARI; Ruchi GUPTA; Amit Kumar VERMA; Sanjeev KUMAR; Yogita KATIYAR (Modern Medicine)
Background: Thyroid gland is afflicted by various pathologies amongst which nodules are the cause of maximum concern because of their malignant potential. With the introduction of high resolution ultrasound and use of Thyroid imaging reporting and data system (TIRADS) classification as a widely used universal grading system, there has been reduced inter-observer variability and increased inter-departmental communication. In this study, we studied the TIRADS ultrasound grading as a screening tool and compared it with the BETHESDA grading on FNAC. Material and methods: 200 patients with thyroid nodules were subjected to ultrasound and USG guided FNAC. Each was assigned a TIRADS and Bethesda grade. Findings were compared to assess the sensitivity, specificity, PPV (positive predictive value) and NPV (negative predictive value) of ultrasound in differentiating benign from malignant nodules. RESULT: Out of 200 nodules examined, 116 nodules belonged to TIRADS 2 while 44, 13 and 27 belonged to TIRADS 3, 4 and 5 respectively. On FNAC, 162 patients belonged Bethesda 2 & 12, 7, 15 and 4 to Bethesda 3, 4, 5 and 6 respectively. The sensitivity, specificity, PPV and NPV of ultrasound were found to be 92.3, 90.8, 60 and 98.75 % respectively. Conclusion: TIRADS is an effective risk stratification system which should be routinely used in our clinical practice as it can predict the possibility of a particular nodule for being malignant to a great extent. Especially keeping in mind its high negative predictive value, FNAC can be deferred in TIRADS 2 patients which form a majority of cases reporting to pathology department for thyroid FNAC.